Bentuk Pemerintahan Islam Perspektif Nahdlatul Ulama` dalam Konteks Keindonesiaan - Mubarok, Mohammad Yazid (Proceedings of Annual Conference for Muslim Scholars, 2019)
The form of the Islamic government became a heated debate again after the chairman of the Indonesian Solidarity Party, Grace Natalie, said that she would not support the adoption of sharia regulations, which were then reported to the police. Therefore, by seeing this kind of phenomenon, it is necessary for the writer to see the perspective of Nahdlatul Ulama, about his views on the form of Islamic government that prevails in Indonesia today. In reality, Nahdlatul Ulama 'actually does not reject the Khilafah system, because that Nahdlatul Ulama' gave the title Waliyul Al-Amr Daruri Bi Al-Syaukah to President Soekarno. NU's rejection of the Khilfah system was caused by circumstances that made it impossible to establish a Khilafah, where each state is currently under the auspices of the nation-state (nation state), coupled with the absence of definite provisions in Islam, which require a form of state and system a certain government, for its adherents. Therefore, the State of Indonesia can be called Darul Islam or an Islamic state, because it was once fully controlled by Muslims, although it was later captured by the infidel invaders (the Netherlands), but the Islamic state remained forever